Endovascular therapies for pulmonary embolism. Issue 4 (April 2021) - Rousseau, Hervé; Del Giudice, Costantino; Sanchez, Olivier; Ferrari, Emile; Sapoval, Marc; Marek, Pierre; Delmas, Clément; Zadro, Charline; Revel-Mouroz, Paul
Abstract: Purpose: The aim of this article is to define the place of new endovascular methods for the management of pulmonary embolisms (PE), on the basis of a multidisciplinary consensus. Method and results: Briefly, from the recent literature, for high-risk PE presenting with shock or cardiac arrest, systemic thrombolysis or embolectomy is recommended, while for lowrisk PE, anticoagulation alone is proposed. Normo-tense patients with PE but with biological or imaging signs of right heart dysfunction constitute a group known as "at intermediate risk" for which the therapeutic strategy remains controversial. In fact, some patients may require more aggressive treatment in addition to the anticoagulant treatment, because approximately 10% will decompensate hemodynamically with a high risk of mortality. Systemic thrombolysis may be an option, but with hemorrhagic risks, particularly intra cranial. Various hybrid pharmacomechanical approaches are proposed to maintain the benefits of thrombolysis while reducing its risks, but the overall clinical experience of these different techniques remains limited. Patients with high intermediate and high risk pulmonary embolism should be managed by a multidisciplinary team combining the skills of cardiologists, resuscitators, pneumologists, interventional radiologists and cardiac surgeons. Such a team can determine which intervention – thrombolysis alone or assisted, percutaneous mechanical fragmentation of the thrombus or surgical embolectomy – is best suited to a particular patient. Conclusions: This consensus document define the place of endovascular thrombectomy based on an appropriate risk stratification of PE. Abstract : Thrombectomy; Pulmonary embolism; Thrombolytic therapy; Pharmacomechanical thrombectomy; Embolectomy.